2018
DOI: 10.1615/plasmamed.2018028327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Temperature on pH and Conductivity of Reverse Osmosis Water Treated with Atmospheric Plasma

Abstract: We believe that the reactions involved in plasma-activated water (PAW) production are a consequence of long-lived reactive oxygen and nitrogen species (e.g., NO, O, OH, ONOO-, and H 2 O 2) that are transferred from the plasma environment to liquid. Based on the assumption of reaction continuity in water treated with atmospheric plasma, we devised an experiment to monitor pH and electrical conductivity in samples of reverse osmosis water, before and after treatment. We used gliding arc discharge that was operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…No change in pH and a significant reduction in ORP of PAW after seven days stored at room temperature was also observed by Joshi et al [35], with a subsequent loss of antibacterial effects. Similarly, plasma activated reverse osmosis water stored at 3 • C or 24 • C did not show any difference in pH values and conductivity after 96 h storage time [36]. The last studies are in agreement with our study that pH was found to be stable during the elongated storage time.…”
Section: Discussionsupporting
confidence: 92%
“…No change in pH and a significant reduction in ORP of PAW after seven days stored at room temperature was also observed by Joshi et al [35], with a subsequent loss of antibacterial effects. Similarly, plasma activated reverse osmosis water stored at 3 • C or 24 • C did not show any difference in pH values and conductivity after 96 h storage time [36]. The last studies are in agreement with our study that pH was found to be stable during the elongated storage time.…”
Section: Discussionsupporting
confidence: 92%
“…ORP is reported to be the principal responsible for destructing microbiological systems' membrane integrity with the fundamental function of affecting the cells' inner and outer membranes [52]. Among the RONS generated in PAW, hydrogen peroxide (H 2 O 2 ) is mainly responsible for the formation of ORP [53] and has a rapid potential for disinfection of liquids [17,54,55].…”
Section: Effect Of Water Dynamic Plasma Activationmentioning
confidence: 99%
“…This plasma water activation technique is inexpensive and environmentally friendly since it is free of chemicals [9]. For this type of application, atmospheric non-thermal plasmas (ANTP) are used, namely, the dielectric barrier discharge (DBD) or the gliding arc plasma jet (GAPJ) [10][11][12][13][14][15][16][17]. The plasma used as a water activating agent can be applied directly submerged in the liquid or applied to millimeters of the liquid's surface [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many active and reactive biochemical substances and radicals arise in the water during the process of plasma activation [16]. In most cases, especially for distilled water [17], this is associated with a massive decrease in pH and a high increase of the oxidation potential.…”
Section: Introductionmentioning
confidence: 99%